Exploring the Implementation of Google Classroom in Online English Language Learning: A Literature Review - Irawan, Rohman Adi; Kuning, Dewi Sri (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2025)
This study aims to explore the implementation of Google Classroom in online English learning, focusing on its impact on student learning outcomes, motivation, and learning independence. The method used was a qualitative descriptive literature study, which analyzed nine scientific articles published between 2019 and 2024. The study collected data from various studies that discussed the use of Google Classroom in English language learning at various levels of education, by identifying the benefits, challenges, and aspects that affect its effectiveness. The results show that the use of Google Classroom significantly improves student engagement, time efficiency, and English learning outcomes, despite challenges related to digital infrastructure such as unstable internet connections and device limitations. Additionally, the platform supports self-paced learning by giving students the freedom to access materials and complete assignments on their schedules. The study also found that Google Classroom facilitates collaboration between students and teachers, improving interaction and communication. The contribution of this research lies in the comprehensive mapping of the effectiveness of Google Classroom in online English learning, as well as providing recommendations for improving digital literacy training for teachers and developing educational infrastructure, in order to maximize the potential of technology in learning.